Advances in Fine Needle Aspiration Cytopathology - Arnouk, Hilal (IntechOpen, 2023)
This book is a collaboration between world-class bench scientists and clinicians in the fields of oncology, surgery, and pathology in which they come together to highlight the diagnostic utility and applications of fine needle aspiration. It discusses the use of this procedure to diagnose various lesions in different organ systems, such as salivary glands, thyroid glands, breast, lungs, liver, and so on. It also examines recent advances in image-guided acquisition, cytological preparations, and ancillary molecular tests as well as the inherent limitations and future directions for the fine needle aspiration technique.